2000
DOI: 10.1080/009841000156619
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Free-Ranging and Captive American Kestrels Under Electromagnetic Fields

Abstract: Wild birds, particularly raptors, commonly use electrical transmission structures for nesting, perching, hunting, and roosting. Consequently, birds are exposed to electromagnetic fields (EMFs). The amount of time that wild reproducing American kestrels (Falco sparverius) were exposed to EMFs was determined, and the effects of EMFs on the behavior of captive reproducing kestrels were examined. Wild kestrels were exposed to EMFs for 25% to 75% of the observed time. On a 24-h basis, estimated EMF exposure of wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…A behavioural study with captive American kestrels reported that birds were more active and alert just prior to egg laying under EMF exposure (Fernie et al, 2000b). This increase in locomotor activity was hypothetically attributed to EMF-induced changes in corticosterone titres (Fernie et al, 2000b). Experimental administration of corticosterone increased egg size in Uta stansburiana lizards (Sinervo and DeNardo, 1996), suggesting a potential link between EMF exposure and the increase in egg size observed in our study.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…A behavioural study with captive American kestrels reported that birds were more active and alert just prior to egg laying under EMF exposure (Fernie et al, 2000b). This increase in locomotor activity was hypothetically attributed to EMF-induced changes in corticosterone titres (Fernie et al, 2000b). Experimental administration of corticosterone increased egg size in Uta stansburiana lizards (Sinervo and DeNardo, 1996), suggesting a potential link between EMF exposure and the increase in egg size observed in our study.…”
Section: Discussionsupporting
confidence: 49%
“…The answer will probably be found when looking at the physiological systems responsible for egg formation (Fernie and Reynolds, 2005). A behavioural study with captive American kestrels reported that birds were more active and alert just prior to egg laying under EMF exposure (Fernie et al, 2000b). This increase in locomotor activity was hypothetically attributed to EMF-induced changes in corticosterone titres (Fernie et al, 2000b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation